Fair tax evasion - Erling Barth; Alexander W. Cappelen; Tone Ognedal (University of Oslo, Department of Economics, 2006)
In this paper we analyse how fairness considerations, in particular considerations of just income distribution, affect whether or not people believe tax evasion can be justified and their willingness to engage in tax evasion. Using data from the Norwegian “Hidden Labour Market Survey” we show that individuals with low wages or long working hours, individuals that are treated unfairly by most tax systems, have a higher probability of justifying tax evasion. The same individuals are also more willing to take home income without reporting it to the tax authorities. These results are consistent with a model in which individuals make a trade-off between economic gains and fairness considerations when they make decisions about tax evasion. Taken together our results suggest that considerations of fair income distribution are important for the analysis of tax evasion.
Keywords: D63; H26; 330; Tax evasion; redistributive taxation; fair income distribution; Einkommensteuer; Steuervermeidung; Einkommensumverteilung; Theorie